Dual anionic substitution engineering for an advanced NASICON phosphate cathode in sodium-ion batteries. (10th June 2021) - Zhao, Xin-Xin; Gu, Zhen-Yi; Guo, Jin-Zhi; Zhao, Chen-De; Wang, Xiao-Tong; Xie, Dan; Li, Wen-Hao; Wu, Xing-Long
Abstract : Dual anionic substitution materials of Na3 V2 (PO4 )2 O2−2 x F1+2 x are prepared using the solid-state method, and the regulation mechanism of different F/O ratios is studied by analyzing the structural evolution, electrochemical performance and reaction kinetics. Abstract : Sodium-ion batteries (SIBs) are prominently used for stationary energy storage due to the abundant resources and low cost of Na. The development of high-performance cathodes for SIBs will be a favorable choice for competing with the market-dominant lithium-ion batteries. Among the various cathodes, Na3 V2 (PO4 )2 O2−2 x F1+2 x (0 ≤ x ≤ 1) materials have become a preferred choice due to their superior structural stability, fast ion transport and high operating potential. Herein, a series of materials with various ratios of F − and O 2− (F/O) are prepared via a high temperature solid-state method, and the tuning mechanism of different F/O ratios is studied in detail by analyzing the structural evolution, electrochemical performance and reaction kinetics of materials. The optimal F/O ratio material Na3 V2 (PO4 )2 O0.6 F2.4 ( x = 0.7) exhibits a favorable rate and cycling performance. The capacity at 20C is equivalent to that of the x = 0 material at 5C, and each cycle decay is 0.040% after 200 cycles at 0.5C. Moreover, the optimized F/O ratio material ( x = 0.7) also demonstrates excellent reaction kinetics, and the Na apparent diffusion coefficient ( D app, Na ) for the high potential region is about 10 −10 –10 −12 cm 2 s −1 . A systematic research of dual anion substitution in phosphates will be useful for the structural design and performance improvement of other cathode materials in SIBs.